Risk of significant cytopenias after treatment with tocilizumab in systemic juvenile arthritis patients with a history of macrophage activation syndrome - Kessler Elizabeth A; Vora Sheetal S; Verbsky James W (BMC, 2012)
Abstract Tocilizumab (TCZ) is the first FDA- approved treatment for systemic juvenile idiopathic arthritis (sJIA). We report 3 cases of cytopenias in children with sJIA treated with TCZ. Two of the children who developed significant cytopenias shortly after initiation of TCZ had a history of macrophage activation syndrome. We raise the possibility that patients with a tendency towards MAS have an increased risk of developing cytopenias when treated with tocilizumab.